Contested Memories: the Scottish Parliament and the 1984–5 Miners' Strike. Issue 2 (May 2015) - Phillips, Jim
<x xml:space="preserve">Abstract</x> The miners' strike of 1984–5 is a site of contested memories. A debate in the Scottish Parliament on the 30th anniversary in March 2014 highlighted three particular points of contention: the economics of coal and the social costs of closures; the strategies of the National Union of Mineworkers and the UK Conservative government; and the question of restorative justice for victimised strikers. This paper examines these controversies, measuring the perspectives of MSPs against the weight of historical evidence. It explores the moral economy of the Scottish coalfields, where closures in the 1960s and 1970s were agreed by the workforce because meaningful employment alternatives existed. Closures in the 1980s violated this moral economy. The paper demonstrates that the financial costs of producing coal were exaggerated in 1984, while the predicted negative social consequences of not producing coal were accurate. It argues that criticisms of NUM strategy in 1984–5 are outweighed by evidence that the Conservative government was attacking the moral economy, seeking to eliminate union voice from decisions about closures. It comments on the victimisation of strikers in 1984–5, arguing that contemporary calls for restorative justice are resisted by the Scottish government partly because the SNP – reflecting the broader mood in the Scottish Parliament – ignores the political salience of social class.